Infestation levels of Aphomia sociella in bumblebees increase with proximity to apiaries and result in lower reproductive output and weaker immune response - Krams, Ronalds; Grigorjeva, Tatjana; Willow, Jonathan; Popovs, Sergejs; Munkevics, Māris; Trakimas, Giedrius; Contreras-Garduño, Jorge; de Souza, André Rodrigues; Adams, Colton B.; Rantala, Markus J.; Garajeva, Samira J.; Sledevskis, Eriks; et al. (Frontiers in Bee Science, 2025)
IntroductionBumblebees are essential pollinators in temperate regions of the northern hemisphere. Niche overlap and competition with honeybees may impose significant stress on bumblebees by reducing nutrient acquisition and increasing the risk of pathogen and parasite spillover from honeybees. One of these parasites is the bumblebee wax moth (Aphomia sociella), whose larvae can be found in bumblebee and wasp nests, as well as weakened commercial honeybee hives (hereafter called apiaries).MethodsUsing Bombus terrestris colonies as experimental models, we expected that young queen and worker bumblebee immunity (measured by encapsulation response) would become weaker under both competitive (i.e., proximity to apiaries) and parasite (A. sociella infestation) pressure and, specifically, that the immunity of bumblebees in closest proximity to apiaries would be weakest in nests infested by A. sociella.Results and discussionWe observed increased infestation, lower reproductive output, and weaker encapsulation response in bumblebee colonies that were near apiaries. Our data provide insights on the ecology of A. sociella infestations where honeybees and bumblebees coexist. Our observations of reduced immune response in bumblebees inhabiting colonies nearer to apiaries are of critical importance, as this reduction in immune response could facilitate additional infestations of other parasites and pathogens within bumblebee colonies.